2008
DOI: 10.1186/1471-2172-9-41
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of CD127low expressing CD4+CD25high T regulatory cells is inversely correlated with human T lymphotrophic virus type-1 (HTLV-1) proviral load in HTLV-1-infection and HTLV-1-associated myelopathy/tropical spastic paraparesis

Abstract: Background: CD4 + CD25 high regulatory T (T Reg ) cells modulate antigen-specific T cell responses, and can suppress anti-viral immunity. In HTLV-1 infection, a selective decrease in the function of T Reg cell mediated HTLV-1-tax inhibition of FOXP3 expression has been described. The purpose of this study was to assess the frequency and phenotype of T Reg cells in HTLV-1 asymptomatic carriers and in HTLV-1-associated neurological disease (HAM/TSP) patients, and to correlate with measures of T cell activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…In accordance with our findings, HTLV-1 symptomatic patients exhibit reduced FOXp3 expression and Treg suppressor function compared with healthy donors, which could explain the marked cellular activation, spontaneous cytokine production, and associated disease development [26,27]. In periodontal tissues, CD4 + CD25 + FOXp3 + cells were found in inflammatory infiltrates in periodontal tissues and were associated with high expression of the regulatory cytokines IL-10 and transforming growth factor b [4].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with our findings, HTLV-1 symptomatic patients exhibit reduced FOXp3 expression and Treg suppressor function compared with healthy donors, which could explain the marked cellular activation, spontaneous cytokine production, and associated disease development [26,27]. In periodontal tissues, CD4 + CD25 + FOXp3 + cells were found in inflammatory infiltrates in periodontal tissues and were associated with high expression of the regulatory cytokines IL-10 and transforming growth factor b [4].…”
Section: Discussionsupporting
confidence: 91%
“…Deregulated immune response due to HTLV-1 infection is associated with adult T cell leukemia and chronic progressive disease of the central nervous system termed HTLV-1-associated myelopathy (HAM)/tropical spastic paraparesis (TSP) [21] and also with T lymphocytic alveolitis, polymyositis, arthritis, uveitis, and sicca syndrome [23]. Indeed, the marked production of T H 1 and proinflammatory cytokines and the expansion of autoreactive T cells observed in HTLV-1-infected patients are in part due to the lack of regulatory T cell function and decreased ability of IL-10 and transforming growth factor b to downmodulate immune response [2,[24][25][26][27][28]. Therefore, HTLV-1 infection can be considered a potential modifying factor in the pathogenesis of PD.…”
mentioning
confidence: 96%
“…Yamano et al has reported that CD4+ CD25+ cells are the predominant viral reservoir in HAM/TSP PBMC and that the decreased Foxp3 expression in this subset was associated with a loss of suppressor function (Yamano et al 2004; Oh et al 2006; Michaelsson et al 2008; Hayashi et al 2008). It was suggested that this decrease of Foxp3 expression (loss of T regulatory cell function) may be involved in persistent T cell activation in lesions of HAM/TSP patients.…”
Section: Location Of Htlv-i Infected Cells and Htlv-i Proviral Expresmentioning
confidence: 99%
“…Notably, only the top 1-2% of these cells (CD4 + CD25 hi ) is considered to be functionally suppressive (13), and this frequency varies physiologically, especially with increased age (14). Several additional markers used to characterize Tregs in healthy donors, including GITR, CD127, and CTLA4, are unreliable here due to their alteration by HTLV-1 related activation (15, 16). …”
Section: Introductionmentioning
confidence: 99%